Androgen receptor splice variants mediate enzalutamide resistance in castration-resistant prostate cancer cell lines - Li, Yingming (2012)
Persistent androgen receptor (AR) transcriptional activity underlies resistance to AR-targeted therapy and progression to lethal castration resistant prostate cancer (CRPC). Recent success in re-targeting persistent AR activity with next-generation androgen/AR axis inhibitors such as enzalutamide (MDV3100) has validated AR as a master regulator during all stages of disease progression. However, resistance to next-generation AR inhibitors limits therapeutic efficacy for many patients. One emerging mechanism of CRPC progression is AR gene rearrangement, promoting synthesis of constitutively-active truncated AR splice variants (AR-Vs) that lack the AR ligand binding domain. In this study, we demonstrate that cells with AR gene rearrangements expressing both full-length and AR-Vs are androgen-independent and enzalutamide-resistant. However, selective knock-down of AR-V expression inhibited androgen-independent growth and restored responsiveness to androgens and antiandrogens. In heterogeneous cell populations, AR gene rearrangements marked individual AR-V-dependent cells that were resistant to enzalutamide. Gene expression profiling following knock-down of full-length AR or AR-Vs demonstrated that AR-Vs drive resistance to AR-targeted therapy by functioning as constitutive and independent effectors of the androgen/AR transcriptional program. Further, mitotic genes deemed previously to be unique AR-V targets were found to be biphasic targets associated with a proliferative level of signaling output from either AR-Vs or androgen-stimulated AR. Overall, these studies highlight AR-Vs as key mediators of persistent AR signaling and resistance to the current arsenal of conventional and next-generation AR-directed therapies, advancing the concept of AR-Vs as therapeutic targets in advanced disease.